(untitled) (American Journal of Business Management, Economics and Banking, 2026)
Finance is a field that deals with issues related to money—such as earning money, managing it, and investing it. Finance can also create centralized and decentralized monetary funds. Therefore, its role and significance depend on the place of monetary relations in the system of economic relations. This article discusses financial analysis, the socio-economic nature of finance, financial theories, public finance, and international financial relations.